The Impact of Education on TB Prevention in Stunted Children in the Working Area of the Kosiwo Health Center, Kepulauan Yapen Regency - Dedy Arisjulyanto; Neny San Agustina Siregar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Tuberculosis (TB) is a serious infectious disease that continues to be a global health challenge, particularly in Indonesia. Children with stunting are at a higher risk of contracting TB due to their weakened immune system caused by malnutrition. This study aims to analyze the impact of education on TB prevention in stunted children in the working area of the Kosiwo Health Center, Kepulauan Yapen Regency. The research method used was a quantitative approach with a quasi-experimental design, involving parents and caregivers of stunted children as respondents. Data were collected through questionnaires administered before and after the educational intervention. A total of 45 participants were selected using a total sampling method. Data were collected before and after the intervention using a validated and reliable questionnaire on children's knowledge of tuberculosis (TB), with a Cronbach's alpha of 0.946 for the TB knowledge questionnaire. The results were analyzed using the Paired T-Test, which showed that the mean knowledge score concerning TB transmission in children was 14.89 before the intervention, increasing by 9.78 points to 24.67 afterward, with a p-value of 0.000, which is below α = 0.05.